Calligrams: A strategic resource for the development of abstraction in international baccalaureate students . - Carrión Cipriano , Gilmer Ever (2023)
Abstract thinking is an indispensable skill for problem solving in any dimension of reality. For this reason, in human development there is a stage where this cognitive ability is best stimulated: adolescence (Piaget, 1972). For this reason, the present study aims to demonstrate that there is a significant relationship between the application of calligrams as a didactic resource and the development of abstraction in international baccalaureate students of COAR-Huancavelica (2022). The population consisted of 151 individuals between 15 and 16 years of age, of which only a sample of 20 was obtained (nonprobabilistic sampling). The methodology applied was a descriptive, no causal correlational design, where the degree of association between variable 1 (didactic resource of calligrams) and variable 2 (development of abstraction) was analyzed. A written test consisting of 12 items was used for the data collection process. The research concludes by accepting the alternative hypothesis; that is, it was shown that both variables are correlated by 0.415.